Implementation of The Position and Responsibilities of Notaries as Public Officials in Carrying Out Their Position So That They Participate in Committing Criminals in Cirebon Regency - Kartikasari, Ice; Wahyuningsih, Sri Endah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the position of Notaries as Public Officials in Carrying Out Their Positions So That They Participate in Carrying Out Criminal Acts in Cirebon Regency and to determine and analyze the Principles of Legal Protection for Notaries as Public Officials in Carrying Out Their Positions So That They Participate in Carrying Out Criminal Acts in Cirebon Regency. The approach method in this study is the sociological legal approach method. The results of the research and discussion in this study are: The Position of Notaries as Public Officials in Carrying Out Their Positions So That They Participate in Carrying Out Criminal Acts in Cirebon Regency in this case is categorized as a party who participated in carrying out criminal acts because Notary S, S.H., M.Kn made a Sale and Purchase Agreement No. 598 dated December 21, 2017 for a plot of land in the Certificate of Ownership No. 1088 covering an area of 4,080 m2, which then caused a dispute and it was suspected that the Notary had colluded as a result of the Notary being dragged into a lawsuit over the deed he made, even in this case, such as the notary Faridah and the defendant Ina Rosaina in Jakarta, they were even sentenced to 2 years in prison with a fine of 1,000,000,000 (one billion) with the alleged criminal act regulated in Article 264 paragraph (1) of the Criminal Code in conjunction with Article 55 paragraph (1) ke-1 of the Criminal Code, Article 3 of the Republic of Indonesia Law Number 8 of 2010 concerning the Crime of Money Laundering in conjunction with Article 55 paragraph (1) 1 ke-1 in conjunction with Article 56 paragraph (1) of the Criminal Code. Therefore, Notaries in carrying out their duties serving the legal acts of the community contain moral idealism which is reflected in the Code of Ethics and UUJN and the Principle of Legal Protection for Notaries as Public Officials in Carrying Out Their Positions So That They Participate in Carrying Out Criminal Acts in Cirebon Regency reflecting the principle of Legal Protection for (Positions) of Notaries in carrying out their duties as Public Officials which are regulated in Article 4 paragraph (2) and Article 16 paragraph (1) letter f UUJN. The principle of legal protection for notaries as public officials in carrying out their positions aims to provide security guarantees and legal certainty for notaries in carrying out their duties, including in the Cirebon Regency area.